Disciple Preaching in the First Generation An Ecological Study - Stevenson, Dwight E. (Reed Lectures, 1969)
Based on the Reed lectures from 1969, Stevenson examines the Old-World origins and the impact of the early American frontier on early Disciples preaching up to the time of the Civil War. He notes the preaching forms that early leaders rejected-mere flowery or rhetorical messages and harangues against established Protestant sects-and what was accepted in its place. Stevenson's essays draw into sharp relief the difference between debate and preaching, a line that has often been blurred within the Stone-Campbell tradition.